Water Supply and Sewerage Services in Ludhiana City: A Study of Financial Constraints. - Bedi, Jasdeep Kaur, Ghuman R.S., and Bhullar, A.S (2013)
The economic health of Ludhiana water supply utility is in a very poor state due to the prevalence of a large number of illegal connections, under recovery of water charges, decline in the real tariffs, wastage of water, consistently increasing cost of supply and the reluctance of the political and administrative managers to improve the economic health of the utility. The revenue of the utilities must cover the expenditure and generate some surplus amount which can be used to initiate new water supply programmes and update the existing supply system. Although the time is not ripe to declare the drinking water strictly as an ‘economic good’ rather it should remain a ‘social good’ yet it must be brought under certain economic and financial regulations to ensure economic and financial sustainability.